2015
DOI: 10.1098/rsos.140386
|View full text |Cite
|
Sign up to set email alerts
|

Opsin transcripts of predatory diving beetles: a comparison of surface and subterranean photic niches

Abstract: The regressive evolution of eyes has long intrigued biologists yet the genetic underpinnings remain opaque. A system of discrete aquifers in arid Australia provides a powerful comparative means to explore trait regression at the genomic level. Multiple surface ancestors from two tribes of diving beetles (Dytiscidae) repeatedly invaded these calcrete aquifers and convergently evolved eye-less phenotypes. We use this system to assess transcription of opsin photoreceptor genes among the transcriptomes of two surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 58 publications
3
46
1
Order By: Relevance
“…Of the differentially regulated genes (> twofold change in expression), 71.7% exhibited decreased expression in the cave species. Similarly, significantly decreased expression levels of three different opsin transcripts were observed in multiple subterranean diving beetle species in comparison with related surface species [33]. We also observed significant decreases in the expression of visual genes in the subterranean population (discussed below), but the general trend toward upregulation in the cave population is difficult to explain.…”
Section: Resultssupporting
confidence: 59%
“…Of the differentially regulated genes (> twofold change in expression), 71.7% exhibited decreased expression in the cave species. Similarly, significantly decreased expression levels of three different opsin transcripts were observed in multiple subterranean diving beetle species in comparison with related surface species [33]. We also observed significant decreases in the expression of visual genes in the subterranean population (discussed below), but the general trend toward upregulation in the cave population is difficult to explain.…”
Section: Resultssupporting
confidence: 59%
“…Changes in Opsin number can be observed even within closely related species that prefer different light conditions, as shown by the comparisons between surface and subterranean species of predatory diving beetles [21*]. However, scorpionflies provide a conflicting example: common scorpionflies (Panorpidae) have somewhat colored bodies and wings but have lost two Opsins (SW and UV) with only one (LW) left, making them monochromats [59,69].…”
Section: Color Vision In Different Insectsmentioning
confidence: 99%
“…1C) [7**,18,19,20]. On the other hand, nocturnal insects have often lost Opsins or have reduced Opsin expression, which can affect an entire phylogenetic branch or just a single species [2,21*]. Some insects exhibit strategies to enhance color vision or regain previously lost sensitivities for certain wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that loss of expression of opsin genes without loss of gene function is explained by the pleiotropic roles of opsin genes [36]. Extensive transcriptomic analysis revealed that three independently evolved subterranean diving beetles lack transcripts of nearly all opsin photoreceptor genes, whereas the two surface beetles showed evidence of transcriptional expression of a full suite of insect visual and non-visual opsin genes [47]. Thus, research on the absence or presence of putative opsin genes from the A .…”
Section: Resultsmentioning
confidence: 99%